Enrolling decisionally incapacitated subjects in neuropsychiatric research - Fins, J J; Miller, F G (CNS spectrums, 2000)
This paper discusses the National Bioethics Advisory Commission's (NBAC's) report on research involving persons with mental disorders that may affect decisionmaking capacity. After placing the NBAC recommendations into their historic context, the authors propose a strategy to enroll decisionally incapacitated subjects into neuropsychiatric research. The authors maintained that their proposed consensus model for research authorization, utilizing subject advocates, fosters valuable clinical research while protecting potentially vulnerable subjects.